Studi tizianeschi : annuario della Fondazione centro studi Tiziano e Cadore. (Pieve di Cadore : Fondazione Centro Studi Tiziano e Cadore, 2003)
The periodical Studi Tizianeschi has the double aim of presenting the new and original scholarship Titian and to keeping readers abreast of current publications by cataloguing the latest studies about his art and life. The insightful papers, written in Italian or English, are accompanied by reviews of books, articles and exhibitions, by reports on the restoration of works and by museum acquisitions, as well as a listing of all events pertaining to the artist. It is a publication that constitutes an excellent guide for all those who – whether amateurs or scholars – want to learn more about Titian.(www.tizianovecellio.it)
Https://www.tizianovecellio.it/studi-tizianeschi-sub/?lang=en
Italiaans
Jaarboeken
Keywords: Titiaan; Fondazione centro studi Tiziano e Cadore